Effect of Disinfection Methods on the Flexural Properties of Auto Polymerizing Resin - Mallikarjun M.; Bharathi M.; Mahesh Babu K.; Rajendra Prasad B.; Goutham P. (Recent Updates in Disease and Health Research Vol. 7, 2024)
This Study evaluated the effect of disinfection methods on the Flexural Properties of Auto Polymerizing Resin (Tooth Colored and Repair Resin). Sterilization and disinfection have become the most popular and widely used methods for the control of infection. Potential sources of transmission of infection from patient to dental technician are impression, impression trays and gypsum casts. Specimens were exposed to microwaves for 15 min and 2% Glutaraldehyde for 10 hours. Specimens stored in Water for 12 hours were used as control. For each procedure, 10 specimens were used. The result indicated that changes in Flexural Strength observed were of no significance for both Tooth Colored and Repair Resin. The Microwave method is a useful alternative to immersion disinfection having the advantage of less time consumption. The study evaluated the effects of chemical (Glutaraldehyde) and microwave sterilization on flexural and impact strengths of auto-polymerising resins used for denture repairs and in fabrications of temporary Crown and bridge restorations. Samples were prepared according to ASTM standards.